Different roles of the Amazon-Orinoco barrier on the genetic structure of two sardine genera from the Western Atlantic Ocean - Ferreira-Araújo, Thais; Hollanda-Carvalho, Pedro; Di Dario, Fabio; Mendes, Liana de Figueiredo; Oliveira, Claudio [UNESP]; Gasparini, João Luiz; Rotundo, Matheus Marcos; Macieira, Raphael M.; Lima, Sergio Maia Queiroz (Springer Nature, 2024)
Three sardine species of Harengula and one of Opisthonema (Clupeiformes, Clupeidae) are known in the Western Atlantic, where the Amazon-Orinoco plume has been recognized as a major biogeographic barrier, albeit permeable to larger and generalist species. Here we used mitochondrial cox1 gene DNA sequences to check the lineage delimitation of both genera, testing the influence of the Amazon-Orinoco barrier (AOB) and marine provinces on their phylogeographic structure. Results indicate that the two genera are differently affected by the AOB, including cryptic speciation in Harengula and population structure in Opisthonema. Harengula show a broad distribution in the Brazilian Province (BRA) distinct from H. clupeola and H. jaguana from the Greater Caribbean Region (GCR). Divergence time between Harengula from the GCR vs. BRA was estimated as about 2.4 Mya, which coincides with the period of increasing sediment and freshwater discharge of the Amazon River in the Atlantic. Results also indicate the existence of a single species of Opisthonema, albeit with population structuring related to the marine provinces. Since species of both genera are relevant to artisanal fisheries and the maintenance of oceanic ecosystems, these results may help in fisheries management of these important marine resources.
Keywords: Clupeiformes; Fisheries; Harengula; Opisthonema; Phylogeography; Population structure